1997
DOI: 10.1002/(sici)1096-9071(199703)51:3<182::aid-jmv7>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of adenovirus DNA in peripheral blood mononuclear cells by polymerase chain reaction assay

Abstract: Adenovirus can establish persistent infections which may reactivate and cause disease in immunocompromised hosts. Lymphocytes have been postulated to serve as a site of adenoviral persistence based upon the ability to isolate adenovirus from tonsils and to detect adenovirus DNA by Southern blot hybridization in peripheral blood mononuclear cells (PBMC). To test this hypothesis, a more sensitive and specific polymerase chain reaction (PCR) assay was developed to detect adenovirus DNA. Two sets of nested primers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 28 publications
2
32
1
Order By: Relevance
“…by guest www.bloodjournal.org From A positive PCR from serum or peripheral blood mononuclear cells has been associated with an adverse outcome in 2 retrospective studies. 21,22 Detection of the virus in blood by PCR was directly related to a fatal outcome in our study, and for the first time, such an association has been demonstrated prospectively. Our study suggests that the isolation of adenovirus from multiple sites is a sequential event, and this is preceded by viremia, as suggested by a positive blood PCR.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…by guest www.bloodjournal.org From A positive PCR from serum or peripheral blood mononuclear cells has been associated with an adverse outcome in 2 retrospective studies. 21,22 Detection of the virus in blood by PCR was directly related to a fatal outcome in our study, and for the first time, such an association has been demonstrated prospectively. Our study suggests that the isolation of adenovirus from multiple sites is a sequential event, and this is preceded by viremia, as suggested by a positive blood PCR.…”
Section: Discussionsupporting
confidence: 62%
“…Second, although it is suspected that the adenovirus can establish latent or persistent infection, the site and nature of latent infection are largely unknown. 21 All of the patients in our study had a positive stool isolate regardless of the other sites of isolation, suggesting reactivation from gut-associated lymphoid tissue. Third, the infections were not clustered and there were no outbreaks.…”
Section: Discussionmentioning
confidence: 78%
“…However, further studies have to unequivocally demonstrate whether or not donors and recipients really are infected with the same AV isolate. Horvath et al 16 detected AV DNA in peripheral lymphocytes in 13 of 17 healthy adults, whereas Flomenberg et al 17 could not detect AV DNA in mononuclear cells of 33 adults. A transmission of AV through transfusions given after SCT seems to be very unlikely since our patients only received leukocyte-filtered blood components.…”
Section: Discussionmentioning
confidence: 96%
“…7 It is possible that, in parallel with CMV, a pre-emptive treatment strategy with ribavi-rin might be considered in high risk patients using a PCR assay to detect adenovirus DNA in peripheral blood mononuclear cells. 17 Adoptive immunotherapy might be a therapeutic avenue worth further consideration, as in CMV or EBV infections. Having failed to salvage four adenovirus-infected T celldepleted stem cell transplant recipients with i.v.…”
Section: Discussionmentioning
confidence: 99%